Exploring experiences of burnout, engagement, and social support networks: a qualitative study of hospital medicine physicians - Robinson, Dea, author; Korte, Russell, advisor; Balgopal, Meena, committee member; Han, Heeyoung, committee member; Maynard, Travis, committee member (Colorado State University. Libraries, 2019)
Studies on burnout and engagement for US physicians have resulted in few changes to improve the lives of affected physicians who suffer from the negative effects of burnout that include negative effects to patient care. Research has suggested that physician social support networks can provide protections against burnout that theoretically would lead to a more engaged physician. This qualitative study was conducted to understand the nature of hospitalist experiences of burnout, engagement and social support networks for 15 hospital medicine physicians (i.e., hospitalists). Two sources of burnout related to hospitalist leaders and hospitalists (non-leader role) emerged: (a) lack of hiring authority, (b) lack of business support, and (c) disruptive peer behavior. Sources of burnout for hospitalists (non-leader) came from: (a) unrealistic expectations from a boss and (b) stress from the employment contracting process, and (c) enough time in the day to finish work. Sources of engagement came from: (a) time spent with patients during difficult diagnosis, (b) appreciation expressed from patients, and (c) meaningful connections with patients. Social support networks for hospitalists were represented by: (a) clinical support, (b) non-clinical support; and (c) leader support. Social support networks were influenced by the quality of relationships hospitalists had with their boss and degree of support received from their leaders. Implications from the study suggested burnout and engagement are separate constructs; engagement is defined differently by hospitalists and their leaders, and sources of stress that lead to burnout need to be identified to enact effective interventions.
Keywords: meaningful work; physician engagement; social support networks; physician burnout; healthcare leadership; physician-patient relationships